The United Nations Security Council at the Forefront of (Climate) Change? Confusion, Stalemate, Ignorance - Hardt, Judith Nora (2021)
In the context of the United Nations Security Council (UNSC), the debate on whether climate change should be included and how has been ongoing since 2007. This article contributes to existing research on this problem by expounding a three-fold analysis. First, it assesses the conceptual approach to the climate-security nexus from the joint statement of 10 UNSC member states in 2020. Second, it critically exposes the confusion of different climate-security conceptions and uncovers shared assumptions of the UNSC-member states in 2020 by comparing their different positions, which makes a soon-to-come agreement likely. Third, it critically evaluates whether the proposal to include climate change into the UNSC will lead to a transformative change of the institution, of the meaning of security, and on how this would correspond to the existential threats outlined in the Anthropocene context. The theoretical framework of analysis draws on critical security studies. It takes as its empirical basis the primary sources of the UNSC debate of 2020 and is also informed by the secondary literature on climate and security and the Earth System Sciences descriptions of the state of the planet.